Effect of Foaming Agent on the Properties of Superporous Hydrogels Prepared via Solution Polymerization Method - Suriati, Ghazali; Najahusna, Adnan (Informatics Publishing Limited, 2017)
Background/Objectives: Superporous hydrogels (SPHs) are three dimensional network polymers that often crosslinked through chemical or physical interactions. It can swell to an equilibrium state and retain a significant amount of water molecule due to the presences of interconnected microscopic pores. The swelling rate of most of the dried hydrogel (i.e. xerogels) typically low and take a longer time to reach equilibrium due to slow water absorption capability. This disadvantage further limits the possible application of the hydrogel to be utilized in various field, includes as drug delivery material and as soil conditioner in agriculture field. Therefore, there is a significant interest in developing synthesis method and the selection of material in preparation of the superporous hydrogel that can exhibit both fast swelling absorption properties.